Social work's histories of complicity and resistance : a tale of two professions - Amadiegwu, Akudo; Bald, Caroline; Campana-Alabarce, Melisa; Copeland, Victoria; Dettlaff, Alan J.; Duarte, Filipe; Gabriel Silva, Pedro; Harms-Smith, Linda; Herrero, María Inés Martínez; Ioakimidis, Vasilios; Ioakimidis, Vasilios; Kuhlmann, Carola; et al. (Book collections on Project MUSE., 2023)
Social work is often presented as a benevolent and politically neutral profession, avoiding discussion about its sometimes troubling political histories. This book rethinks social work's legacy and history of both political resistance and complicity with oppressive and punitive practices. Using a comparative approach with international case studies, the book uncovers the role of social workers in politically tense episodes of recent history including the anti-racist struggle in the US and the impact of colonialism in Australia, New Zealand and Canada. As the de-colonisation of curricula and Black Lives Matter movement gain momentum, the fascinating book skilfully navigates social work's collective political past while considering its future.